Adapting the patch-cut system to implement forest assisted migration - Philippe Nolet; Martin Béland; Christian Messier; Christian Messier (Frontiers in Forests and Global Change, 2024)
As the Anthropocene tightens its grip on the world, forests are facing escalating disturbance rates, tree mortality, degradation and risks of catastrophic collapses. A popular and controversial proposition is to enhance forests’ response diversity by adding novel tree species with missing functional traits through forest assisted migration (FAM). Beyond tests of the survival and growth of southern species or provenances in colder regions and studies of the socio-ecological challenges facing FAM, little interest has been paid to the silvicultural system for FAM implementation. Yet, the topic could influence its biological success, social acceptability, and economic feasibility. For example, southern light-intolerant tree species introduced into northern uneven-aged forests may experience a lack of light availability. Likewise, implementing FAM in clearcuts raises social acceptability issues. The patch-cut system combines advantages of even- and uneven-aged systems useful for FAM; however, perhaps due to the difficulty of its operationalization, it is rarely used. We propose a new way to implement the patch-cut system, enabling from the get-go to plan the location and timing of treatment of each patch in a stand. We discuss the advantages that this revisited patch-cut system presents for FAM: (i) the testing of various planting environments, (ii) easy monitoring in an adaptative management context where each patch is a replicate of a repeated-measure experiment and (iii) low intensity planting for efficient future dispersion of species adapted to a changing climate. We end with a call for the development of an international network of FAM trials within the revised patch-cut system.